The Translation of English Activity Verbs Found in Turtle and Dolphin Story - I Gusti Bagus Narabhumi; I Nyoman Sedeng; Putu Sutama (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
In trilingual kidsâ€™ story book entitled â€œTurtle and Dolphinâ€ by Dunkle et al (2012), the English text has both Indonesian and Balinese equivalences. This study aims at revealing the translation procedures applied to the English text especially the activity verbs and also the correlation between the translation procedures and the translation shifts that happen as the result of translations. The English activity verbs as the data in this study are collected using documentation method, the analysis is done by applying descriptive qualitative method and the result is shown using the combination of informal and formal methods. The result shows that literal translation is the most frequent translation procedure applied to translate ST into Indonesian (91%) and Balinese (77%). However, there are several English activity verbs transferred into mental verbs, nouns, and prepositions in the TT. Furthermore, when literal translations are applied the shifts that appear are intra-system shifts (36%). When transpositions are applied, the shifts that appear are class shifts (100%). When modulations are applied the shifts that appear are intra-system shifts (60%). Lastly, when adaptations are applied, the shifts that appear are intra-system shifts (37, 5%).